Perception of the Faculty about the Importance of the Dimensions of Organizational Climate of Selected State Agricultural Universities - Borah , Sayanika (Indian Journal of Extension Education, 2019)
The study was conducted in four state agricultural universities of India viz. PAU Punjab (North); ANGRAU, Andhra Pradesh (South); AAU, Assam (East) and MPAU, Rajasthan (West) to study the variations in perceptions of the faculty and administrators regarding the importance of dimension of organizational climate along with their perception of prevailing and expected organizational climate. The data collected from the 216 faculty members using a scale developed on 13 dimensions viz. communication, management of rewards, interpersonal relationships, control and supervision, orientation, decision making, leadership, policies and rules, innovation, physical facilities, team work, monetary gains and accountability/ evaluation revealed that communication followed by leadership, team work and physical facilities were the most important dimensions according to the faculty who ranked monetary gains, accountability/ evaluation, management of rewards and control and supervision as least important.
Keywords: Perception; Importance; Organisational climate dimensions; Faculty and state agricultural university